SERS- and electrochemically active 3D Plasmonic liquid marbles for molecular-level spectroelectrochemical investigation of microliter reactions - Koh, Charlynn Sher Lin (2020)
Liquid marbles are emergent microreactors owing to their isolated environment and the flexibility of materials used. Plasmonic liquid marbles (PLMs) are demonstrated as the smallest spectroelectrochemical microliter‐scale reactor for concurrent spectro‐ and electrochemical analyses. The three‐dimensional Ag shell of PLMs are exploited as a bifunctional surface‐enhanced Raman scattering (SERS) platform and working electrode for redox process modulation. The combination of SERS and electrochemistry (EC) capabilities enables in situ molecular read‐out of transient electrochemical species, and elucidate the potential‐dependent and multi‐step reaction dynamics. The 3D configuration of our PLM‐based EC‐SERS system exhibits 2‐fold and 10‐fold superior electrochemical and SERS performance than conventional 2D platforms. The rich molecular‐level electrochemical insights and excellent EC‐SERS capabilities offered by our 3D spectroelectrochemical system are pertinent in charge transfer processes.